Molecular markers for analysis of plant genetic diversity - Nam, Vu Tuan; Hang, Pham Le Bich; Linh, Nguyen Nhat; Ly, Luu Han; Hue, Huynh Thi Thu; Ha, Nguyen Hai; Hanh, Ha Hong; Hien, Le Thi Thu (Vietnam Journal of Biotechnology, 2021)
Genetic diversity plays an important role in diversity conservation at multiple levels and supports to monitor and assess genetic variation. In plants, genetic diversity provides the ability to adapt and respond to environmental conditions that helps plants to survive through changing environments. Genetic diversity analyses based on molecular genetic markers are effective tools for conservation and reintroduction of rare and endangered species. In recent years, the development of various chemical and molecular techniques for studying genetic diversity has received great attention. While biochemical markers are primarily used in the diagnosis of pathogens, DNA markers have been developed and widely applied for identification of species and population based on the genotype of an organism that is more stable and not easily affected by the environmental factors. PCR-based molecular marker tools, such as restriction fragment length polymorphisms (RFLPs), random amplified polymorphic DNA (RAPD), simple sequence repeats (SSRs) are used for analysing the difference in the targeted DNA sequences. With the rapid and robust development of genomic sequencing technology it is now possible to obtain and analyse DNA sequences of the whole genome of studied organisms. However, each type of DNA markers has different principles, as well as the pros and cons of specificity. In this article, we review methods and point out DNA markers, which are considered as reliable and widely used tools for the detection of genetic variation. In addition, we present the application of DNA marker in analysing genetic diversity of wild, domestic and medicinal plants, as well as some perspectives on the future of DNA marker’s application in the analysis of genetic diversity.